Exploiting the Facile Oxidation of Evaporated Gold Films to Drive Electroless Silver Deposition for the Creation of Bimetallic Au/Ag Surfaces. Issue 1 (10th September 2013) - Plowman, Blake J.; Field, Matthew R.; Bhargava, Suresh K.; O'Mullane, Anthony P.
<x xml:space="preserve">Abstract</x> The golden road: The facile synthesis of gold‐silver bimetallic surfaces was investigated through the spontaneous decoration of silver on evaporated gold films. This spontaneous reaction was found to be driven by the oxidation of the gold surfaces at potentials lower than that expected for bulk gold, providing a simple method of metal decoration to create bimetallic surfaces.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>